(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The non-steroidal anti-inflammatory drug diclofenac (DCF) has a harmful effect on plants and algae by several studies. It is one of the most often used and found pharmaceuticals in water bodies, as the total biomass of phytoplankton and many phytoplankton are used as indicators in the aquatic habitat, their communities are sensitive to changes in their environment. The aim of this study is to assess the effect the interactive effect of copper and diclofenac on Planktothrix sp. Data provided by this research shows information on the interactive effect of copper and diclofenac on Planktothrix sp. At 500µg/L of diclofenac and 2.5µg/L of copper using the experimental design; Dry weight/cell density, pigment content, enzyme activity (POD, MDA, ROS, GST) and total protein content. Dry weight/cell density was recorded highest in the control treatment (CoR) with total weight of 2.14g, showing that diclofenac and copper inhibits the growth of Planktothrix sp. Reactive oxygen species ROS was highest in the control treatment (CoR) on day 7 (0.075µg/ml), glutathione S transferase (GST) was recorded highest on day 14 of Diclofenac and copper treatment (DiRCuR) having 37.04 µg/ml, peroxidase activity POD was highest on day 14 of copper (CuR) and diclofenac + copper (DiRCuR) treatment with 0.122µg/ml showing that diclofenac and copper singly and in combined form affects the antioxidant enzymes of Planktothrix sp. from the results of these study, it shows that there is a synergistic effect of copper and diclofenac on the growth of Planktothrix sp.